Effect of advanced footwear technology spikes on lower limb kinetics and sprint performance - Gerlach, M.; de Graaf, M. L.; Boström, K. J.; Wagner, H. (Footwear Science, 2025)
Performance enhancement is a key goal in the design and evaluation of athletic footwear. Recently developed Advanced Footware Technology Spikes (AFT Spikes), which combine advanced foams and/or air pods with a rigid curved plate, have attracted attention through their performance improvements. However, studies on possible associated injury risk are rare, despite reports of increased Achilles tendon pain. Therefore, our aim was to investigate potential performance benefits, and especially potential increased loads associated with the use of AFT Spikes. Twelve experienced sprinters completed four 30 m flying sprints with a preceding 15 m acceleration phase using two different types of spikes: traditional spikes (Trad Spikes) and AFT Spikes. Sprint times and kinematic data were recorded. A musculoskeletal model was used to estimate corresponding joint contact forces (JCFs) of the hip, knee, and ankle, as well as the muscle forces of the ankle plantarflexors. These kinetic variables were normalised to the body weight of the subjects and examined using generalised linear mixed models. Results showed significant improvements of 1.32% in sprint times when athletes wore AFT Spikes compared to Trad Spikes. JCFs of the ankle and the plantarflexor force increased significantly (5.25%BW and 7.18%BW, respectively) while sprinting with AFT Spikes. No significant differences were found in the JCFs of the knee and hip joints. Individual responses to the change in footwear varied widely. Although the performance benefits of AFT Spikes were remarkable, athletes should consider the increased loads when using AFT Spikes. If future studies confirm the link between AFT spikes and an increased risk of injury, it may be advisable to introduce the use of AFT Spikes gradually to allow the musculoskeletal structures time to adapt.